Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/ijosup.2016.9
|View full text |Cite
|
Sign up to set email alerts
|

Does gastric bypass surgery change body weight set point?

Abstract: The relatively stable body weight during adulthood is attributed to a homeostatic regulatory mechanism residing in the brain which uses feedback from the body to control energy intake and expenditure. This mechanism guarantees that if perturbed up or down by design, body weight will return to pre-perturbation levels, defined as the defended level or set point. The fact that weight re-gain is common after dieting suggests that obese subjects defend a higher level of body weight. Thus, the set point for body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 83 publications
0
9
0
3
Order By: Relevance
“…It is well accepted that metabolic surgery is the most effective strategy to treat obesity and its associated comorbidities (Hao et al 2016 ; Schauer et al 2017 ). The review by Nicoletti et al summarizes genes which have been identified to be epigenetically altered after metabolic surgery.…”
Section: Epigenetic Plasticity: Influence Of Interventions On Epigenementioning
confidence: 99%
“…It is well accepted that metabolic surgery is the most effective strategy to treat obesity and its associated comorbidities (Hao et al 2016 ; Schauer et al 2017 ). The review by Nicoletti et al summarizes genes which have been identified to be epigenetically altered after metabolic surgery.…”
Section: Epigenetic Plasticity: Influence Of Interventions On Epigenementioning
confidence: 99%
“…In addition, long-term adaptation and a stable body weight after weight loss following bariatric surgery has been proposed to reflect a permanent re-setting of the body weight set point, restoring “normal” leptin signaling (or its downstream signals) in the hypothalamus 60 , 61 . Accordingly, after bariatric surgery, the proposed re-programming of the body weight defense mechanisms at a lower body weight was not associated with increased hunger feelings or reduced EE 61 . By contrast, animal data suggest no increase in hypothalamic leptin sensitivity after weight loss due to bariatric surgery, questioning the idea of re-programming a set point 60 .…”
Section: What Is the Human Evidence Of Body Weight Control?mentioning
confidence: 99%
“…Research shows that hormones controlling satiety, appetite and hunger are responsible for this 11 . Although the exact mechanisms are still being investigated, there is evidence that the set-point regulating body weight indeed is permanently set at a lower level 12,13 . After surgery, appetite is reduced and then followed by weight Interestingly, symptoms of diabetes may improve immediately after surgery, and many patients will have normal blood sugar levels and require less medication long before the weight loss has occurred 14 .…”
Section: Obesity Treatment: Metabolic Surgerymentioning
confidence: 99%